Analysis of Students' Chemical Literacy on Class X Electrolyte and Non-Electrolyte Solutions at SMAN 2 Batang Anai - Nadiatul Khusna; Eka Yusmaita (Universitas Riau, 2023)
The evaluation results on electrolyte and non-electrolyte solution materials at SMAN 2 Batang Anai still have not reached the Minimum Completeness Criteria (KKM). As many as 50% of the 130 students are still incomplete in the evaluation of learning on electrolyte and non-electrolyte solutions, so it is necessary to evaluate students so that the teacher knows the causes of students' scores being below the KKM. This study aims to analyze the chemical literacy level of class X students of SMAN 2 Batang Anai in electrolyte and non-electrolyte solution materials using the Rasch model with the Ministep application according to the level of scientific literacy developed by Bybee. This research is a descriptive research with a quantitative approach with a sample of 75 students. The results showed that students in class X SMAN 2 Batang Anai dominated at 2 levels of chemical literacy, namely nominal scientific literacy (52%) and functional scientific literacy (44%). Rasch analysis shows that 96% of students have a negative measurement value with an average student measurement value of -2.63 logit. This shows that the ability of students' chemical literacy in electrolyte and non-electrolyte solution materials is relatively low.